Prognostic role of bone erosion in orbital RMS: a report from the European Pediatric Soft Tissue Sarcoma Study Group (EpSSG) - Di Carlo, Daniela; Fichera, Giulia; Minard-Colin, Veronique; Coppadoro, Beatrice; Orbach, Daniel; Cameron, Alison; Albiac Ramos, Monica; Ben Arush, Myriam; Merks, Johannes H. M.; Bisogno, Gianni (Frontiers in Oncology, 2024)
BackgroundOrbital rhabdomyosarcoma (RMS) is often limited to the orbital cavity and has a favorable prognosis. In some cases, the tumor can erode the orbital bone and behave as a parameningeal RMS (PM-RMS); thus, it is treated more intensively. However, the current protocols do not provide any guidance on how to consider different grades of bone erosion (BE) that can vary widely, hampering a uniform classification and the subsequent treatment assignment. With the aim of clarifying the role of BE as a risk factor, we analyzed patients with orbital RMS included in the European Pediatric Soft Tissue Sarcoma Study Group (EpSSG) protocol.MethodsWe retrospectively analyzed the radiological reports of 199 patients with orbital RMS (PM or not) and defined three grades of BE: minimal (thinning of the bone), moderate (focal bone lysis), and extensive (complete cortical destruction).ResultsBE was present in 55 of the 199 (27.6%) patients, which was classified as minimal in 27, moderate in 7, and extensive in 21. Tumors with extensive BE were more frequently large (>5 cm, p = 0.0008) and invasive (T2, p = 0.001). With a median follow-up of 70.4 months (range = 7.1–167.7), a total of 183 patients are alive, with 5-year event-free survival (EFS) and overall survival (OS) rates of 76% (95%CI = 69.2–81.3) and 92% (95%CI = 86.7–94.8), respectively. Patients without any BE had better OS (95% vs. 81%, p = 0.001), but not EFS. Patients with no/minimal/moderate BE had better EFS and OS compared with patients with extensive BE [EFS of 78.1 (95%CI = 71.1–83.5) vs. 57.1 (95%CI = 33.8–74.9), p = 0.0114, respectively, and OS of 94.0 (95%CI = 89.2–96.8) vs. 71.1 (95%CI = 46.6–85.9), p < 0.0001, respectively]. Events and metastatic relapses (in all cases CNS/meningeal) were more frequent in patients with extensive BE.ConclusionsOnly those patients with orbital RMS and extensive BE should be considered as PM and should be treated accordingly.